Food labeling in Argentina. Decoding impacts on the Argentine Food Code - Pinto, Mauricio; Buccheri, Mauricio; Martín, David (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2024)
This work aims to analyze the characteristics of the legislative codification technique in Argentina, and whether, since the enactment of the Food Code to the present, this technique has been affected by a decoding normative evolution, considering the food labeling regime a particular study case. As a result, three lines of legislative alteration or modification distorting the mentioned technique re identified. This generates inconsistencies and ambiguities in the legislation, and consequent negative effects on the application, compliance and understanding of food regulations in the industry. Highlights: The Argentine Food Regime was based on the legislative technique of codification. It can be stated that the Argentine Food Code has legislative action lines in tension with the codification legislative technique. Since the enactment the Food Code there has been a decoding evolution, with negative effects on the application, compliance and understanding of the regulations in the food industry.